The Microenvironment Is a Critical Regulator of Muscle Stem Cell Activation and Proliferation - Nguyen, John H.; Chung, Jin D.; Lynch, Gordon S.; Ryall, James G. (Frontiers in Cell and Developmental Biology, 2019)
Skeletal muscle has a remarkable capacity to regenerate following injury, a property conferred by a resident population of muscle stem cells (MuSCs). In response to injury, MuSCs must double their cellular content to divide, a process requiring significant new biomass in the form of nucleotides, phospholipids and amino acids. This new biomass is derived from a series of intracellular metabolic cycles and alternative routing of carbon. In this review, we examine the link between metabolism and skeletal muscle regeneration with particular emphasis on the role of the cellular microenvironment in supporting the production of new biomass and MuSC proliferation.